2000
DOI: 10.1128/aem.66.11.4764-4771.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Random Mutagenesis of theErwinia herbicola tyrRGene for High-Level Expression of Tyrosine Phenol-Lyase

Abstract: Tyrosine phenol-lyase (Tpl), which can synthesize 3,4-dihydroxyphenylalanine from pyruvate, ammonia, and catechol, is a tyrosine-inducible enzyme. Previous studies demonstrated that the tpl promoter of Erwinia herbicola is activated by the TyrR protein of Escherichia coli. In an attempt to create a high-Tpl-expressing strain, we cloned the tyrR gene of E. herbicola and then randomly mutagenized it. Mutant TyrR proteins with enhanced ability to activate tpl were screened for by use of the lac reporter system in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 61 publications
1
49
0
Order By: Relevance
“…The same results were obtained for five independently constructed strains. This was surprising, because the expression of the aroP gene is known to be strongly repressed by tyrosine but not by tryptophan (9,22,36,(46)(47)(48)55) and the AroP system is known to exhibit almost equal affinity for the three aromatic amino acids (5,36). At present, the reason for this phenomenon is unclear.…”
Section: Vol 186 2004 the Liv-i/ls System As A Phenylalanine Transpmentioning
confidence: 86%
“…The same results were obtained for five independently constructed strains. This was surprising, because the expression of the aroP gene is known to be strongly repressed by tyrosine but not by tryptophan (9,22,36,(46)(47)(48)55) and the AroP system is known to exhibit almost equal affinity for the three aromatic amino acids (5,36). At present, the reason for this phenomenon is unclear.…”
Section: Vol 186 2004 the Liv-i/ls System As A Phenylalanine Transpmentioning
confidence: 86%
“…One such mutant, TyrR V67A Y72C E201G , was found to increase Tpl expression effectively, 10) and when the mutant gene was introduced into E. herbicola, the resulting strain showed improved L-dopa productivity. 11) However, the addition of L-tyrosine to the medium was still required to achieve the maximum productivity of the strain (Fig.…”
Section: Abstract: 34-dihydroxyphenyl-l-alaninementioning
confidence: 99%
“…In a preliminary experiment, we observed that the introduction of pACYC177 carrying the tutB gene into an E. coli strain with the ⌽(tplЈ-Јlac) gene (14) enhanced the tyrosine-induction ratio of tpl by twofold, but neither the phenylalanine-nor the tryptophan-mediated induction ratio was elevated. Since the expression of tpl is positively regulated by the TyrR protein (22) and its coeffectors (three aromatic amino acids), even though the magnitude of activation is quite different among the three ligands (13,28), the above observation implied that the tutB gene might encode a tyrosine transporter. In order to characterize the tutB gene product, an E. coli strain deficient in the uptake of all aromatic amino acids (5) was constructed (MG1655 ⌬aroP mtr24 ⌬pheP ⌬tna ⌬tyrP) and used for transport assays.…”
mentioning
confidence: 99%
“…It has been shown that the F plasmid is stably maintained in Erwinia species (3). The Tpl contents of the cells grown under tyrosine-induced and non-induced conditions were determined by immunoblotting (13), and the results are presented in Fig. 4.…”
mentioning
confidence: 99%
See 1 more Smart Citation